Bamboo Massage Tool as a Learning Media of Body Massage Care Course - Indah Eges Wahyuni; Ade Novi Nurul Ihsani; Suyitno Suyitno (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
This study aimed to determine the validity of the development of bamboo massage tool as a learning media for Body Massage Care course regarding product validity tests, sensory tests, and preference tests. The research method used is Research and Development (RD), using seven development steps with a quantitative approach. The research subjects are 25 students receiving body care course using media. Data analysis techniques use descriptive percentages. The research results on the product validity test aspect obtained an average total value of 85.38% of the six indicators: shape, size, quality, strength, function and benefits, and ease of use. The sensory test results were 86.02% of the four indicators: shape, size, ease of use, and functions and benefits. The preference test results were 91.06% of the four indicators, namely shape, size, ease of use, and quality. The conclusions from the research based on the validity, sensory, and preference tests are very feasible.